The impact of high‐fidelity simulation on knowledge, critical thinking, and clinical decision‐making for the management of pre‐eclampsia. Issue 3 (21st June 2020) - Akalin, Ayse; Sahin, Sevil
Abstract: Objective: To investigate the impact of high‐fidelity simulation on nursing students' knowledge, critical thinking, and clinical decision‐making in the management of pre‐eclampsia, and to explore the students' views and learning experiences. Methods: A mixed‐methods design study was conducted on 107 third‐year nursing students. The students were randomly assigned to the control group (n=54) or the experimental group (n=53). The students in the experimental group attended the simulation training using a high‐fidelity simulator, while the students in the control group attended only the classical training on "the management of pre‐eclampsia." Results: Knowledge ( P <0.001), critical thinking ( P <0.05), and clinical decision‐making ( P <0.05) scores of students in the experimental group increased after the simulation. In the focus group interviews, five themes were identified: learning development; closing the gap between theory and practice; confident decision‐making and self‐confidence; professional preparation; and recommendations. Conclusion: High‐fidelity simulation is efficacious for improving the management of pre‐eclampsia among nursing students. Abstract : High‐fidelity simulation training is an effective method for students to improve their knowledge, critical thinking, and clinical decision‐making regarding the management of pre‐eclampsia.